Investigation of Dengue Fever Cases with Associated Risk Factors at Suburbs of Peshawar in 2018 - Minallah, Asim; Azam, Naila; Mansoor, Eisha; Akram, Fahd; Niazi, Saifullah; Baig, Mirza Amir (Pakistan Armed Forces Medical Journal, 2022)
Objective: To assess the magnitude of the dengue fever outbreak, evaluate risk factors and recommend control measures.Study Design: Case-control study.Place and Study of Study: Suburb area of Peshawar Pakistan, from May to Jun 2018.Methodology: A desk review of available records and active case findings was conducted. A case was defined as a fever of >38 0C for 2 to 10 days with minimum two of the following; headache, rash, retro-orbital pain, myalgia and bleeding in a resident of suburb area of Peshawar and a positive NS-1 test. Age and sex-matched controls were identified from the same locality. A structured questionnaire was used to collect information about cases and controls.Results: A total of 140 cases were identified (28 cases through active case finding). Males were 124 (88%) while females were 16 (12%). The total number of residents in that area was around 4500, the attack rate was 3.1%. The most affected age-group was 21-30 years (AR=5.03%). Out of 140 cases, 88 had open water containers in the house (OR=3.9, 95%CI=2.5-6.0), and 84 cases had larvae present in their households (OR=2.5, 95%CI=1.6-3.8). Regular use of repellents and screened doors and windows showed a protective effect.Conclusion: The presence of open water containers inside the house served as breeding grounds for the vector and was the most probable cause of the outbreak. Regular use of repellents was shown to be protective.